Rediseño de los planos de emergencia y evacuación en las estaciones de la gerencia de exploración y producción del área de Shushufindi. (EPPETROECUADOR). - Manzanillas Cueva, Oscar Antonio (2013)
In the present research work the current emergency and evacuation plan is redesign by implementing and restructuring what is necessary, to maintain and identify a procedure of potential emergency situations and accidents to safeguard the integrity and life of workers, the same as, the maintenance of facilities of "Shushufindi Exploration and Production Management Stations Area" to the potential risks that may occur and how to respond to them. In this work we found that, there are areas with significant risks to the safety of personnel working in the stations, the main risks are: fire, falls to the same level, falls at different levels, exposure to toxic substances and explosions. Among the main reasons that cause an accident are: lack of attention to maintenance plans, failure to comply with safety standards listed in some of the areas of the company, overconfidence of staff performing routine tasks in hazardous areas, and unconventional facilities. The main of the unwanted effects in the stations under study is the death of staff followed by mutilations, burns, poisoning, illnesses and property losses, the frequency of mild unwanted effects (cuts surface bumps, drops, scratches, etc..) is medium event rate; the serious unwanted effects (death, mutilation, poisoning, burns) have a low event rate. Due to this it is important to increase a system of fire detection and automatic fire sprinklers in areas of washing tanks and upwelling in the six stations in the Shushufindi area, one of a Fire Hydrant Equipped (BIE) in the lighter area of the six Shushufindi field stations, build a system equipped with fire hydrants and automatic sprinklers exclusively for the gas station located at the central station. Increase outside a fire hydrant in the area of automotive workshop and the production winery in the central station.